2017
DOI: 10.1093/bja/aex128
|View full text |Cite
|
Sign up to set email alerts
|

High intraoperative inspiratory oxygen fraction and risk of major respiratory complications

Abstract: NCT02399878.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 37 publications
4
141
1
1
Order By: Relevance
“…Secondary analysis did not show any significant differences between groups in the odds of atelectasis (odds ratio 1.11, 0.75 to 1.66; P=0.60), pneumonia (0.95, 0.61 to 1.48; P=0.82), or respiratory failure (1.27, 0.78 to 2.07; P=0.34). Additional prospective trials are needed to determine the proper risk/benefit ratio of a higher FiO 2 , as a recent large database study of 74 000 surgical patients associated an intraoperative FiO 2 of 80% with a doubling of the odds of major pulmonary complications (odds ratio 1.99, 1.72 to 2.31; P=0.05) 106. Given these results, use of a high FiO 2 only as necessary to correct hypoxia may be prudent, as lower concentrations may help to prevent atelectasis.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Secondary analysis did not show any significant differences between groups in the odds of atelectasis (odds ratio 1.11, 0.75 to 1.66; P=0.60), pneumonia (0.95, 0.61 to 1.48; P=0.82), or respiratory failure (1.27, 0.78 to 2.07; P=0.34). Additional prospective trials are needed to determine the proper risk/benefit ratio of a higher FiO 2 , as a recent large database study of 74 000 surgical patients associated an intraoperative FiO 2 of 80% with a doubling of the odds of major pulmonary complications (odds ratio 1.99, 1.72 to 2.31; P=0.05) 106. Given these results, use of a high FiO 2 only as necessary to correct hypoxia may be prudent, as lower concentrations may help to prevent atelectasis.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…The median Injury Severity Score (ISS) was 10 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and the first recorded Glasgow Coma Scale (GCS) score in the trauma bay was 13 [3][4][5][6][7][8][9][10][11][12][13][14][15] (Table 1).…”
Section: Re Sultsmentioning
confidence: 99%
“…10 Of note, the only trial on trauma patients (traumatic brain injury [TBI]) that was included did not report mortality data but, conversely, showed that degree of disability was significantly higher at 6 months in the group that had received restrictive oxygen compared to liberal oxygen. 12,13 For example, a recent retrospective study found hyperoxaemia to be an independent risk factor for ventilator associated pneumonia. 12,13 For example, a recent retrospective study found hyperoxaemia to be an independent risk factor for ventilator associated pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is routine practice during general anaesthesia (GA) to administer more than the 21% oxygen in which we mostly spend our lives. It is essential to understand the physiology underlying this practice if we are to keep patients safe by avoiding both hypoxaemia and hyperoxia during GA. 1 Four pathophysiological changes occur, which explain the answer to the question posed in the title of this article.…”
mentioning
confidence: 97%